The Decomissioning Of The Moro Islamic Liberation Front Combatants In Camp Darul Arham, Butig Lanao Del Sur And It’s Implication To Peace - Diamaoden, Arsalan A.; Abdulhakim, Haimanah R.; Camama, Sittie Roselainie P. (Future Science / FSH-PH Publications, 2021)
Alongside the roadmap toward the creation of the Bangsamoro is an implementation of Normalization Process by both the Government of the Philippines (GPH) and the Moro Islamic Liberation Front (MILF) which mandates among others the decommissioning of MILF forces and weaponry. As a critical part of the similarly critical normalization process, decommissioning shall be a process of putting the weapons of the MILF beyond use and a process of allowing a smooth transition for MILF combatants to productive civilian life. In line with this, this paper aims to: (a) track the socio-demographic profiles of the combatants; (b) examine the perceptions of the combatants in the decommissioning; (c) describe the role of the Independent Decommissioning Body (IDB) in the decommissioning process and challenges encounter; (d) draw implication from the findings of the study to peace building. The study utilized the explorative-evaluative research design that employed the qualitative descriptive approach in the interpretation of data to one hundred (100) combatants of Darul Arham and IDB staff. A researcher-designed survey questionnaire was used to elicit necessary information. Results show that the combatants highly perceived socio-economic assistance specifically financial, social development, and economic and sustainable livelihood assistance to be extended to them as they are being decommissioned. The study recommends for the strengthening of measures for the both parties, the GPH and the MILF, to promote and guarantee free movement of IDB and create an environment free of fear and of intimidation so it can fulfill its part in the normalization process.